Emerging theranostic applications of carbon dots and its variants. Issue 2 (19th May 2021) - Ray, Priyanka; Moitra, Parikshit; Pan, Dipanjan
Abstract: In recent years, carbon dots (CDs), that is, carbon nanoparticles less than 10 nm in size with unique molecular properties including photoluminescence, biocompatibility, and water dispersibility, have been widely used in various fields of nanobiotechnology. This review article aims to describe the recent progress on CD research with a focus on their chemical composition and varieties as well as a comparative section on graphene quantum dots. The following sections shed light on the synthetic routes towards the fabrication of CDs followed by an elaborate description of their emerging applications in theranostics. Finally, a perspective is provided to indicate the major roadblocks for the translation of CDs from research laboratories to the clinics. This article thus aims to update the latest results in this rapidly developing field and offers crucial insights to inspire novel and exciting research in this domain. Abstract : Carbon dots have been widely used in various fields of nanobiotechnology due to their unique molecular properties including photoluminescence, biocompatibility, and water dispersibility. This review article aims to describe the recent progress on carbon dot research with a focus on their chemical composition and varieties with an elaborate description of their emerging applications in theranostics. ​